Pre-Digested Protein Enteral Nutritional Supplementation Enhances Recovery of CD4+ T Cells and Repair of Intestinal Barrier in HIV-Infected Immunological Non-Responders - Geng, Shi-Tao; Zhang, Jian-Bo; Wang, Yue-Xin; Xu, Yu; Lu, Danfeng; Zhang, Zunyue; Gao, Ju; Wang, Kun-Hua; Kuang, Yi-Qun (Frontiers in Immunology, 2021)
AIDS patients with immune non-response are prone to malnutrition, intestinal barrier damage, thus aggravating chronic immune activation and inflammation. However, nutrition interventions targeting malnutrition may be beneficial to restore immune function, improve clinical outcomes, and reduce mortality remains largely unclear. This work aimed to evaluate the efficacy of a nutrition supplement in HIV-infected immune non-responders (INRs). The subjects received an oral supplementation of a pre-digested protein nutrition formula for three months. We show that the CD4+ T and CD8+ T cell counts were significantly increased after supplementation of the pre-digested enteral nutritional supplement. Among all pro-inflammatory cytokines in the serum, only IL-1β level was significantly decreased, while TNF-β was significantly increased (P < 0.05). The levels of intestinal mucosal damage markers, diamine oxidase (DAO), D-lactic acid (D-lactate), and lipopolysaccharide (LPS), decreased significantly (P < 0.05) after the nutritional intervention. Moreover, at month 3 after intervention, the body weight, body mass index, albumin, and hemoglobin of all subjects were significantly increased (P < 0.05). The correlation analysis demonstrated a significantly negative correlation of CD4+ T cell count with levels of DAO (r = -0.343, P = 0.004), D-lactate (r = -0.250, P = 0.037), respectively, and a significantly positive correlation of IL-1β level with levels of DAO (r = 0.445, P < 0.001), D-lactate (r = 0.523, P < 0.001), and LPS (r = 0.622, P < 0.001). We conclude that the pre-digested enteral nutrition supplement is effective for HIV-infected INRs.